Effect of high energy ball milling on strengthening of Cu-ZrO2 nanocomposites. Issue 5 (1st April 2019) - Abu-Oqail, A.; Wagih, A.; Fathy, A.; Elkady, O.; Kabeel, A.M.
Abstract: In this paper, copper matrix nanocomposites reinforced by 5 and 10 wt% ZrO2 particles were produced by mechanical milling technique at different milling times. The produced nanocomposite powders were investigated by X-ray diffraction technique and transmission electron microscopy. The effect of high energy ball milling on the morphology, microstructure and microhardness of the produced composites has been investigated. After that cold compaction was applied to the prepared powders under a pressure of 700 MPa and sintered at 950 °C for 2 h in hydrogen atmosphere. The results showed that increasing milling time improves microhardness of the prepared nanocomposites. The microhardness of Cu-10%ZrO2 after 20 h milling is 3.76 times larger than pure Cu. This improvement is attributed firstly to the presence of ZrO2 nanoparticles in addition to the improvement coming from the grain refinement and crystallite size reduction occurred due to mechanical alloying. So, in spite of the crystallite size of Cu-10%ZrO2 nanocomposite is reduced to 10.75 nm compared to 105.5 nm for pure Cu, the presence of ZrO2 nanoparticles plays a major role on mechanical properties improvement.